Essays in expectation driven business cycle and wage polarization - Fidia Farah, Quazi (Kansas State University, 2018)
This dissertation investigates two essential features of the US economy. First, it explores how news about future productivity changes business cycle fluctuations. Using the a representative agent model, it shows that implementation labor in workplace organization could be an important channel through which news about the fundamentals can realistically generate US business cycle fluctuations. Further this idea is extended using the perspective of sunspot fluctuations. In particular, the model can lead to multiple equilibria under specific parameterizations. Second, a general equilibrium model has been developed with heterogeneous agents to explain the wage polarization feature of the US labor market, particularly how the price of an important technology is connected to lifetime earnings of agents and affects their college decisions. The following summarizes the three chapters of my dissertation. The first chapter which I co-authored with Dr. Blankenau, argues that purchasing investment goods does not directly increase the productive capacity of a business. Changes in the business through the installation of capital, worker training, and workplace reorganization are often required. These changes themselves are not easily automated. Change requires workers. We build a model where investment requires a complementary labor input. This mechanism is embedded in a representative agent model with capacity utilization, adjustment costs, and separable preferences. We show that this environment can yield positive co-movement between consumption, investment, and labor hours when the economy experiences a news shock about future productivity, thus providing an additional channel through which news shocks can generate key business cycle features. The second chapter is an extension of the first chapter. I investigate the indeterminacy in a representative agent model with implementation labor and increasing returns in production. First, my analysis shows that a representative agent with implementation labor can exhibit increasing returns to scale. Then I show that self-fulfilling beliefs of agents lead to business cycle fluctuations in which multiple equilibria can arise under specific parameterizations. Specifically, implementation labor in the production of capital is the highly important, necessary condition for the self-fulling equilibrium outcome. The third chapter, which is also a joint work with Dr. Blankenau, discusses the wage polarization feature of the US labor market. We build a general equilibrium model with heterogeneous agents, showing how wage polarization can emerge when the price of computer capital falls. Consequently, we find the share of the population with a college degree decreases. Our findings are consistent with recent empirical data that show a U-shaped wage growth pattern in the US as well as a slower growth rate of college-educated workers despite the high returns of investing in education. In the model, we assume that each agent is born with a portfolio of skills. Specifically, each agent can provide manual labor, routine labor, and abstract labor and must decide how much of each to provide. An agent can increase efficiency in all types of labor by attending college. All three types of labor are valued in the labor market at an endogenously determined wage rate. Computer capital is a substitute for routine labor. As its price falls and its quantity increases, agents with a relative aptitude for routine labor no longer find it advantageous to attend college. Since routinization of tasks harms middle-income agents, the model has government policy implications for observed wage polarization.
Keywords: Implementation labor; Indeterminacy; Increasing returns to scale; Wage polarization; Education choiceNews driven business cycles